The effect of the type of organic matter and a source of phosphorous on the growth, yield of corn (Zea mays L.) under different levels from phosphorous in gypsum soil - Nashmi Ahmed Hilal; Noor AL-Dean Mohammed (Al-Qadisiyah Journal of Pure Science, 2021)
A biological experiment was carried out for the purpose of knowing the effect of the type of organic matter, source and level of phosphorous on the growth and yield of corn (Zea mays L.) in gypsum soil. The experiment was carried out in one of the agricultural fields in Salah al-Din Governorate / Al-Alam district in the year 2019. The study included three factors (type of organic fertilizer, phosphorous source and phosphorous level). The factor included the type of organic fertilizer (not adding Z, compost K and sheep waste S), while the second factor included the source of phosphate fertilizer (Triple super phosphate T, diammonium phosphate D), and the third factor included phosphorous levels (0, 90, 180 and 270) kg P ha-1. The experiment was carried out in three replications according to a randomized complete block design (RCBD). Sheep manure outperformed compost in all growth and yield traits, and diammonium phosphate fertilizer outperformed Triple le super phosphate, and the level (270) kg P ha-1 was superior to the rest of the addition levels in all growth and yield traits. The interaction between sheep manure and diammonium phosphate fertilizer at the level of addition (270) kg P ha-1 gave the highest average in the dry weight of the vegetative mass after 45 and 75 days of planting, it reached (55.50 and 130.81) gm plant-1, respectively, Chlorophyll content in leaves (52.80) SPAD and grain yield reached (8119) kg ha-1.